1998
DOI: 10.3346/jkms.1998.13.5.495
|View full text |Cite
|
Sign up to set email alerts
|

Massive pulmonary hemorrhage in newborn infants successfully treated with high frequency oscillatory ventilation

Abstract: Massive pulmonary hemorrhage (MPH) in newborn infants is a catastrophic event with a fatal result. The aim of this study was to assess the efficacy of high frequency oscillatory ventilation (HFOV) as a rescue therapy for MPH in newborn infants. Eighteen newborn infants with MPH refractory to conventional mechanical ventilation were treated with HFOV. Changes in oxygenation were assessed using arterial-alveolar oxygen tension ratio (a/APO2) and oxygenation index (OI) during HFOV. The most common underlying diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 0 publications
1
18
0
Order By: Relevance
“…Hence their mean GA (26.8 AE 2.6 weeks) and mean birth weight (867 AE 263 g) were lower than those reported by Ko et al, who included full-term newborn infants. 27 Similar to other reports, the most common underlying cause of MPH in this study was PDA, in 10 of 18 (59%) patients. [1][2][3]27 In the seven babies who did not have echocardiogram prior to their death, PDA could not be excluded as the cause for MPH, especially in the two infants who had group B streptococcus infection and clinical signs of PDA.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Hence their mean GA (26.8 AE 2.6 weeks) and mean birth weight (867 AE 263 g) were lower than those reported by Ko et al, who included full-term newborn infants. 27 Similar to other reports, the most common underlying cause of MPH in this study was PDA, in 10 of 18 (59%) patients. [1][2][3]27 In the seven babies who did not have echocardiogram prior to their death, PDA could not be excluded as the cause for MPH, especially in the two infants who had group B streptococcus infection and clinical signs of PDA.…”
Section: Discussionsupporting
confidence: 90%
“…There is little data in the literature about HFV treatment of infants with respiratory failure secondary to PH. [27][28][29] Ko et al reported the efficacy of HFOV in newborns with PH; 13 of 18 (72%) of their patients responded to the HFOV and survived. 27 During their HFOV course, none of the responders developed air-leak syndrome, IVH, or hemodynamic compromise.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, HFOV is considered less effective in an obstructive lung condition like a pulmonary hemorrhage, and few preliminary studies aimed at analyzing the effect of HFOV in respiratory distress secondary to pulmonary hemorrhage in VLBW infants have been conducted. 15e17 Ko et al 16 reported that 13 (72%) of 18 of their patients responded to HFOV and survived, and their OI decreased significantly at 1 hour after HFOV therapy. 16 Alkharfy et al achieved a 59% of survival rate (10/17), and OI improved significantly at 3 hours after HFOV therapy.…”
Section: Discussionmentioning
confidence: 97%
“…15e17 Ko et al 16 reported that 13 (72%) of 18 of their patients responded to HFOV and survived, and their OI decreased significantly at 1 hour after HFOV therapy. 16 Alkharfy et al achieved a 59% of survival rate (10/17), and OI improved significantly at 3 hours after HFOV therapy. 17 In our study, none of the patients died within 24 hours of severe pulmonary hemorrhage under HFOV therapy.…”
Section: Discussionmentioning
confidence: 97%
“…HFOV is nowadays accepted worldwide as a rescue mode for patients who do not respond to traditional ventilation, those with different types of air leaks and also those with hemorrhagic pulmonary edema. 5 Besides, in newborn infants with persistent pulmonary hypertension, nitric oxide administered during HFOV is more effective than when used with traditional ventilation. 6 Almost twenty years later, in the era of noninvasive ventilation return, HFOV may probably find its place in this field.…”
Section: High Frequency Ventilation In Neonatology:twenty Years Latermentioning
confidence: 99%